Humiliatio memoriae. Humiliated lives and memories in Franco's-repression archives (Tempo e Argumento, 2022)
This article focuses its object of study on a historical source that can be considered a paradigm of the documents and registers created by authoritarian regimes. In this case, we are dealing with the documentation that the Franco regime initiated against its enemies during and after the Spanish Civil War. It is common within these processes to find personal and intimate writings that are used against their authors. Paying attention to these personal writings forces us to develop a method to reconstruct the fragmentary episodes of the past and reintegrate them into the historical narrative, in a different way to that which has been proposed by the archive as an institution that perpetuates the roles of the regime that originates these documents. The aim of the dictatorial regime was to condemn, humiliate and eliminate the enemy. However, it went further. The regime also intervened in the memory that would remain after the death of each of these people. This text is a sample of this situation. The analysis is based on one of the personal writings that were seized as evidence in one of these trials against the enemies. The very materiality of this document is used to act against its author and denigrate not only her life at the time, but also the memory she left behind for the future.
Keywords: Spanish Civil War; Franco dictatorship; memory; archive; history